SIMILARITIES IN DIFFERENT COUNTRIES CULTURE - Xudayqulova , Azizaxon Nayimjonovna; Orziyeva, Nargiza Oripovna; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
Globalization opened up the world and let people from different parts of the world enjoy what other cultures had to offer. People can pick up new languages and incorporate various cultures into their daily lives, resulting in the development of new ways of doing things. Around the world, different cultures have unique ways of doing things that may seem strange to outsiders. From a global viewpoint, some traditional cultures stand out because they are connected to past civilizations